Managing Oracle Fusion applications - Bingham, Richard (Richard John) (New York McGraw-Hill, 2011)
"From Oracle Press--expert techniques for effectively managing Oracle Fusion Applications. Managing Oracle Fusion Applications explains how to use a comprehensive range of tools, services, and worked best practices, organized into an easy-to-use and practical toolbox, to manage Oracle Fusion Applications--the integrated suite of next-generation enterprise applications that combine the best capabilities from Oracle's extensive product portfolio. Written by a member of the Oracle team designing the support strategy for Oracle Fusion Applications, this is the first and only book on the topic. Effective system management increases application up-time, improves performance, and lowers the total cost of ownership. This Oracle Press guide demonstrates how to achieve these goals.Complete coverage of Oracle Fusion Applications management: Oracle Fusion Applications Product Overview; Oracle Fusion Applications Technical Overview; Successful Enterprise Application Management; Oracle Fusion Applications Lifecycle; Oracle Fusion Applications Management Toolbox; Reliability Management Toolbox; Availability Management Toolbox; Performance Management Toolbox; Optimization Management Toolbox; Governance Management Toolbox; Planning for the Future"--Provided by publisher.
"The book provides four main benefits to the reader. It provides background information about Fusion Applications, which is useful whether you are creating an implementation plan, looking at future uptake, or simply improving your knowledge. Second, it forms a practical reference guide for those running Fusion Applications. Third, it complements the existing documentation and training material, all in the context of application management, and lastly, it helps you understand the need for and content of a high quality Fusion Applications management strategy and plan"--Provided by publisher.
Machine generated contents note: Chapter 1: A Fusion Applications Product Overview -- Chapter 2: A Fusion Applications Technical Overview -- Chapter 3: Successful Enterprise Application Management -- Chapter 4: The Fusion Applications Lifecycle -- Chapter 5: The Fusion Applications Management Toolbox -- Chapter 6: The Reliability Management Toolbox -- Chapter 7: The Availability Management Toolbox -- Chapter 8: The Performance Management Toolbox -- Chapter 9: The Optimization Management Toolbox -- Chapter 10: The Governance Management Toolbox -- Chapter 11: Getting and Staying Healthy -- Chapter 12: Planning for the Future -- Appendix: Further Reading.
Includes index.
Keywords: Oracle Fusion applications; Database management; Software engineering -- Management; Service-oriented architecture (Computer science); Electronic commerce -- Computer programs